Desarrollo de estación de monitoreo para la evaluación integral del desempeño de sistemas bipv usando instrumentación virtual. (2006)
This paper reports on the development of a system, along with a description of the development of the associated equipment, for measuring the parameters characterizing the quality of electrical power generated by a grid-connected PV system. The determining of quality parameters such as normal voltage operating range, waveform distortion, frequency, voltage flicker and power factor was achieved through the implementation of Virtual Instruments (VI’s); using the graphic programming soft-ware LabVIEWTM. The system employed the developed VI’s integrated with a data acquisition card and one FieldPoint system from National Instruments. Testing revealed the developed system to be reliable and suitable for studies related to monitoring the electrical power supplied by a grid-connected PV system. Monitoring of the power supplied, by a grid-connected PV system, to a local grid during a time frame of one month, indicated that the developed system complied with all the specifications demanded for such systems by National and International standards.